Risk of neonatal drug withdrawal after intrauterine co-exposure to opioids and psychotropic medications: cohort study. (2nd August 2017) - Huybrechts, Krista F; Bateman, Brian T; Desai, Rishi J; Hernandez-Diaz, Sonia; Rough, Kathryn; Mogun, Helen; Kerzner, Leslie S; Davis, Jonathan M; Stover, Megan; Bartels, Devan; Cottral, Jennifer; Patorno, Elisabetta
Abstract : Objectives  To assess the impact of in utero co-exposure to psychotropic medications and opioids on the incidence and severity of neonatal drug withdrawal. Design  Observational cohort study. Setting  Nationwide sample of pregnancies in publicly insured women in the US, nested in the Medicaid Analytic eXtract (2000-10). Participants  201 275 pregnant women with public insurance who were exposed to opioids around the time of delivery and their liveborn infants. Interventions  In utero exposure to psychotropic medications, in particular antidepressants, atypical antipsychotics, benzodiazepines, gabapentin, and non-benzodiazepine hypnotics (Z drugs), with prescriptions filled within the same time window as prescriptions for opioids. Main outcome measure  Diagnosis of neonatal drug withdrawal in infants exposed in utero to opioids and psychotropic medications compared with opioids alone. Results  The absolute risk for neonatal drug withdrawal ranged from 1.0% in infants exposed in utero to prescription opioids alone to 11.4% for those exposed to opioids co-prescribed with gabapentin. Among neonates exposed in utero to prescription opioids, the relative risk adjusted for propensity score was 1.34 (95% confidence interval 1.22 to 1.47) with concomitant exposure to antidepressants, 1.49 (1.35 to 1.63) with benzodiazepines, 1.61 (1.26 to 2.06) with gabapentin, 1.20 (0.95 to 1.51) with antipsychotics, and 1.01 (0.88 to 1.15) with Z drugs. In utero exposure to two or more psychotropic medications along with opioids was associated with a twofold increased risk of withdrawal (2.05, 1.77 to 2.37). The severity of the withdrawal seemed increased in neonates exposed to both opioids and psychotropic medications compared with opioids alone. Conclusions  During pregnancy, the use of psychotropic medications in addition to prescription opioids is common, despite a lack of safety data. The current findings suggest that these drugs could further increase the risk and severity of neonatal drug withdrawal.